Factors predicting patient-reported functional outcome scores after humeral shaft fractures. Issue 4 (April 2015) - Shields, Edward; Sundem, Leigh; Childs, Sean; Maceroli, Michael; Humphrey, Catherine; Ketz, John; Gorczyca, John T.
Abstract: Purpose: The aim of this study was to determine patient variables that are independent predictors of validated functional outcome scores after humeral diaphyseal fractures. Methods: Adult patients with humeral shaft fractures were retrospectively recruited from a level 1 trauma centre over an 8-year period. Basic demographic information was obtained along with Disabilities of the Arm, Shoulder and Hand (DASH), Simple Shoulder Test (SST) and Short Form 12 (SF-12) physical component summary (PCS) and mental component summary (MCS). Regression analysis was performed to identify patient factors associated with satisfactory outcomes, defined as DASH < 21; SST ≥ 10; PCS ≥ 40; and MCS ≥ 40. Of 95 eligible patients, 77 were recruited. Participants had an average age of 47 ± 20 years. Forty-five patients were treated with surgery and 32 healed non-operatively. The average follow-up was 48 ± 29 months. Results: Satisfactory DASH scores decreased with increase in age (odds ratio (OR) 0.95; P  = 0.023). Satisfactory SST scores were more likely in patients without a history of psychiatric illness (OR 6.3; P  = 0.01). Satisfactory SF-12 PCS scores were more likely with no psychiatric history (OR 12; P  = 0.007) and in patients with private insurance (OR 11.4; P  = 0.03), but these scores decreased with rising Charlson comorbidity index (CCI; OR 0.50; P  = 0.023). Satisfactory SF-12 MCS scores increased in the absence of psychiatric history (OR 39; P  = 0.003), and decreased with rising CCI score (OR 0.54; P  = 0.035). Analysis of patients younger than 50 years of age ( n  = 38) revealed that the absence of psychiatric history increased the odds of satisfactory DASH scores (OR 10.4; P  = 0.04). Patients aged ≥50 ( n  = 39) had worse DASH scores with increasing age (OR 0.89; P  = 0.037), better SST scores with middle-third fractures compared to proximal (OR 7.8; P  = 0.039), better SF-12 PCS with no psychiatric history (OR 16.1; P  = 0.018) and worse scores with rising CCI (OR 0.50; P  = 0.036), while rising CCI decreased the odds of satisfactory SF-12 MCS scores (OR 0.47; P  = 0.046). Treatment modality, associated fractures and classification as "high energy" mechanism were not associated with outcome. Conclusion: Patient age, history of psychiatric illness, insurance type, fracture location and Charlson comorbidity index scores had a statistically significant effect on patient-reported functional outcomes following treatment of humeral shaft fractures, regardless of treatment modality, injury mechanism and associated fractures. The impact of these variables may be age dependent.